Model Graf Kompatibel di Persimpangan Islamic Center (IC) Mataram Lombok - Bulqis Nebulla Syechah; Dessy Zahwa Hairunnisa; Mifta Fadila; Dara Puspita Anggraeni (EVOLUSI: JOURNAL OF MATHEMATICS AND SCIENCES, 2023)
The purposes of this study were to determine the form of compatible graph from the flow of traffic model’s result at the junction, to calculate the optimal total waiting time at the intersection using compatible graph, and to determine the result calculation of the optimal total of waiting time based on the compatible graph on the settings that have been applied. The results of this study were obtained in the form of the compatible graph from the flow of traffics model’s result at Langko-Airlangga-Udayana-Pejanggik crooroad in Mataram, and the optimal total of waiting time at Langko-Airlangga-Udayana-Pejanggik four-junction which was obtained in the field was 291 seconds, while using compatible graph was 100 seconds. The result calculation of the optimal total of waiting time based on the compatible graph was more optimal (minimal) than based on the settings that have been applied.